Harmonic Elimination Using STATCOM for SEIG Fed Induction Motor Load - Satyanarayana Gorantla; Goli Ravi Kumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Non-linear loads connected to distribution system induce harmonics in to source components and the presence of harmonics in source components affects the performance of other sensitive loads connected at the same point. Induction motor load for drive system should be operated with variable frequency and variable voltage for its speed control. To vary the voltage and frequency, induction motor is fed from an inverter. This total drive set-up constitutes non-linear load type and will be the source of harmonics. This paper depicts the suppression of harmonics with STATCOM in distribution system when induction motor load is fed from SEIG (singly excited inductin generator). STATCOM is controlled with simple synchronous reference frame theory and the results are shown for source current, load current. THD in source current and load current was also shown for the said system. System for single-phase and three-phase induction motor drive was developed and results are shown using MATLAB/SIMULINK software.